Pet finder website development - Ong, Seng Hao (2020)
The name of this project is called Pet Finder Website Development where a pet finding website named “Pet-Search” will be delivering in the end of this project. This project seeks to create a cost-efficient pet finding website with some functions that enhance the effectiveness and efficiency for people to find their lost pets. This website provides all of the necessary tools that a pet finder website must contained with some added features. The aim of this project is to provide people ease of searching lost pets with no difficulties. Several functionalities are implemented in the website including refine searching function, where user can do refine searching to filter out the lost pets and save a lot of time. Besides, posting lost pet poster function, a function that allow users to post their lost pet‟s information to the platform. As there is a lot of missing pet cases happened nowadays and the found rate keep remain low. This website will provide a simple and effective platform for people to search for their missing pets. The clear design of interface and easy use of features of this website make users understand easily how this website work and how to use features in simple steps. After reviewing some similar websites, research and analyze is done to better understand the pet finding website. A list of functionalities, system design architectures and design diagram are obtained and can be further enhanced to achieve the criteria including effectiveness, efficiency and cost-efficient of the system. The features require improvement constantly for ease of use in this Pet-Search website.